Determinasi Debt to Equity Ratio, Quick Ratio, dan Inventory Turnover terhadap Risiko Financial Distress - Diaraprilliana; Yusuf, Muhammad; Gurendrawati, Etty (Indonesian Journal of Accounting and Governance, 2024)
The main focus of this study is to analyze the impact of Debt to Equity Ratio (DER), Quick Ratio (QR), and Inventory Turnover (ITO) on financial distress in manufacturing companies in the LQ45 index in the period 2020-2023. Financial distress refers to the company's difficulty in meeting its financial obligations. This study uses the financial statements of companies in the LQ45 index for the period under study. Multiple linear regression analysis is applied to test the relationship between DER, QR, and ITO with financial distress. This study found that DER has a negative effect on financial distress, so companies with higher debt ratios tend to be better able to avoid financial distress. Conversely, QR has a positive effect on financial distress, which means that companies with greater liquidity are at greater risk of facing financial distress. Meanwhile, ITO has no significant effect on financial distress